Remembering Medgar Evers : Writing the Long Civil Rights Movement - Gwin, Minrose (Book collections on Project MUSE., 2013)
As the first NAACP field secretary for Mississipi, Medgar Wiley Evers put his life on the line to investigate racial crimes (including Emmett Till's murder) and to organize boycotts and voter registration drives. On June 12, 1963, he was shot in the back by white supremacist Byron De La Beckwith as the civil rights leader unloaded a stack of "Jim Crow Must Go" T-shirts in his own driveway. His was the first assassination of a high-ranking public figure in the civil rights movement.